Impact of guanidine-containing backbone linkages on stereopure antisense oligonucleotides in the CNS. Issue 10 (2nd February 2022) - Kandasamy, Pachamuthu; Liu, Yuanjing; Aduda, Vincent; Akare, Sandheep; Alam, Rowshon; Andreucci, Amy; Boulay, David; Bowman, Keith; Byrne, Michael; Cannon, Megan; Chivatakarn, Onanong; Shelke, Juili Dilip; et al.
Abstract: Attaining sufficient tissue exposure at the site of action to achieve the desired pharmacodynamic effect on a target is an important determinant for any drug discovery program, and this can be particularly challenging for oligonucleotides in deep tissues of the CNS. Herein, we report the synthesis and impact of stereopure phosphoryl guanidine-containing backbone linkages (PN linkages) to oligonucleotides acting through an RNase H-mediated mechanism, using Malat1 and C9orf72 as benchmarks. We found that the incorporation of various types of PN linkages to a stereopure oligonucleotide backbone can increase potency of silencing in cultured neurons under free-uptake conditions 10-fold compared with similarly modified stereopure phosphorothioate (PS) and phosphodiester (PO)-based molecules. One of these backbone types, called PN-1, also yielded profound silencing benefits throughout the mouse brain and spinal cord at low doses, improving both the potency and durability of response, especially in difficult to reach brain tissues. Given these benefits in preclinical models, the incorporation of PN linkages into stereopure oligonucleotides with chimeric backbone modifications has the potential to render regions of the brain beyond the spinal cord more accessible to oligonucleotides and, consequently, may also expand the scope of neurological indications amenable to oligonucleotide therapeutics. Lay Summary: In this study, the authors explore the impact of nitrogen-containing (PN) backbones on oligonucleotides that promote RNase H-mediated degradation of a transcript in the central nervous system (CNS). Using Malat1, a ubiquitously expressed non-coding RNA that is predominately localized in the nucleus, and C9orf72, a challenging RNA target requiring a more nuanced targeting strategy, as benchmarks, they show that chimeric oligonucleotides containing stereopure PS and one of the more promising PN backbones (PN-1) have more potent and durable activity throughout the CNS compared with more traditional PS-modified molecules in mouse models. They demonstrate that potency and durability benefits in vivo derive at least in part from increased tissue exposure, especially in more difficult to reach regions of the brain. Ultimately, these benefits enabled the authors to demonstrate pharmacodynamic effects on Malat1 and C9orf72 RNAs in multiple brain regions with relatively low doses.